Efforts to Improve Mathematics Learning Outcomes Material Properties of Spatial Structures using the Prolem Based Learning (PBL) for Class IV Students at SDN 1 Srebegan - Herning Sri Harjanti (Universitas Sebelas Maret, 2022)
The aim of this research is to determine and describe the improvement in learning outcomes for class IV students on the properties of spatial structures using the problem based learning model for class IV students at SDN 1 Srebegan, the demonstration method and real object media. The research carried out was Class Action Research (PTK) in 2 cycles, with two meetings in each meeting. Each stage of the cycle is planning, implementation, observation and reflection. Each cycle a pretest and posttest are held to determine student progress. In cycle 1, out of 12 students, 8 students completed the test with a percentage of 75%. In the second cycle, all students completed with a percentage of 100%. These results indicate that using the Problem Based Learning (PBL) learning model can improve mathematics learning outcomes regarding the properties of space in class IV students at SDN 1 Srebegan.